La politique extérieure canadienne vue de l'Europe. Fin de siècle pour les rapports canado-européens ? - Hettmann, Jens (Études internationales, 1996)
Moving towards the end of the twentieth century, relations between Canada and Europe are not exempt of changes which concern practically all of the issues and contain a number of risks that can potentially provoke or aggravate conflicts between these two long-time partners. If relations between them can be seen on the one hand as "extraordinary" because of their sharing of common values and objectives, they can also be considered as "ordinary" inasmuch that both do not seem oblivious to resort to geo-economic violent measures. This paper will examine the nature of Euro-Canadian relations and their recent orientations and identify some of the factors underlying their evolution in order to assess whether these special relationships will be maintained as well as their capacity to influence world events.